(untitled) (International Journal of Mathematics and Physics, 2022)
The dependences of the spectra of radiation-induced attenuation (RIA) of light in a pure-silica core (PSC) optical fiber (OF) during and after gamma-irradiation up to 590 kGy at a dose rate of 7.6 Gy/s in the near infrared range have been investigated. It was shown that starting with an absorbed dose of 100 kGy, the RIA at 1550 nm becomes larger than at 1310 nm due to an increase in long-wavelength (LWL) RIA. The absorption band, with a maximum at a wavelength near 1800 nm, responsible for the LWL RIA is fully defined for the first time. At an absorbed dose of 590 kGy at wavelengths of 1310 and 1550 nm, the RIA is 14.1 and 23.3 dB/km, respectively. During 3.5 years of annealing of the OF at room temperature the RIA in the entire spectral range of 1100-1700 nm decreases by 40-50%.